Anticonvulsant activities of Quercus infectoria (galls) and Trewia nudiflora (seeds) in Nepalese varieties - Kathayat, Kamal Singh; Pokhrel, Bishal; Bhattarai, Ramesh; Thapa, Nabin; Amgain, Kapil; Bhandari, Ravin (Janaki Medical College Journal of Medical Science, 2022)
Background and objectives: Epilepsy is defined as the heterogeneous, synchronized abnormal electrical discharge from the brain area. The numerous synthetic antiepileptic drugs currently available are ineffective to many patients and plant-derived drugs could be an alternative. The aim of this study was to evaluate anticonvulsant activities of Quercus infectoria (galls) and Trewia nudiflora (seeds) found in Nepal. Materials and methods: Anticonvulsant activity was carried out using Isoniazide-induced clonic convulsion (INH 250 mg/kg) using rat model. Onset and duration of clonic convulsion, percentage protection and death were observed. Results: T. nudiflora showed a dose dependent hindrance on the onset of clonic convulsions when compared with the control group. Treatment with higher doses of T. nudiflora (400 mg/kg) showed significant increase (p < 0.01) in latency of clonic convulsions whereas, lower dose showed significant increase (p < 0.05) in latency of clonic convulsion. The extract of T. nudiflora protected 25% of animals from convulsion at a dose 400 mg/kg. However, Q. infectoria did not display dose dependent delay on the onset of clonic convulsion, Q. infectoria (100 and 400 mg/kg) showed insignificant increases in latency of clonic convulsions. The extract of Q. infectoria protected the 25% of animals when used at a lower dose of 100 mg/kg. Positive control group treated with diazepam at a dose 4 mg/kg showed 100% protection from clonic seizures and death. Q. infectoria (100 mg/kg) T. nudiflora (400 mg/kg) and Diazepam (4 mg/kg) showed significant decrease (p<0.01) in seizure duration (s). Q. infectoria (400 mg/kg) and T. nudiflora (100 mg/kg) showed significant decrease (p < 0.05) in seizure duration compared to control group (Normal saline 10 ml/kg). Study reports the antiepileptic effects Q. infectoria and T. nudiflora. Conclusion: The methanolic extract galls of Q. infectoria and seeds of T. nudiflora showed protective effect on Isoniazide induced convulsion.